The excavation (Scottish Historical and Archaeological Internet Reports, 2006)
A description of the methodology is followed by an archaeological description of the roundhouse, two hearths or ovens and a four-post structure. Stratigraphic relationships across the site were destroyed by ploughing and drainage systems.